(untitled) (Journal of Environmental Science and Natural Resources, 2019)
Mushroom is getting very popular in Bangladesh with serving notable nutritional components to the consumers. Nutritional components have been explored but yet not explored the socio-economic values and related factors affecting to the it cultivations. Thus, the major attempt of the present study was to assess the profitability and the factors affecting the production of mushroom (Oyster mushroom). Primary data were collected from 50 mushroom farmers of the selected four areas of Savar Upazila under Dhaka district. The area was purposively selected considering the concentration of different mushroom farmers. From the view point of Gross Margin and net return, mushroom is a profitable business that found in the study area. Gross cost, gross returns and undiscounted BCR per year of mushroom production per season was Tk. 284009.62, Tk. 463954.80 and 1.63 respectively. The Cobb-Douglas function was applied for analyzing the functional effect on mushroom production. The functional analysis indicated that per year gross returns were significantly influenced by the level of education, use of human labor and number of spawn (seed) packets of the farmers. J. Environ. Sci. & Natural Resources, 11(1-2): 83-86 2018